Correlation of diabetes and adverse outcomes in hospitalized COVID-19 patients admitted to a tertiary hospital in China during a small-scale COVID-19 outbreak - Yu Li; Guanni Li; Jiahong Li; Zirui Luo; Yaxuan Lin; Ning Lan; Xiaodan Zhang (PeerJ)
Background The aim of this study was to investigate the impact of diabetes on mortality and adverse outcomes in COVID-19 patients and to analyse the associated risk factors. Methods This is a retrospective cohort study in 500 hospitalized patients with COVID-19 infection (214 with diabetes and 286 without diabetes) admitted to a tertiary hospital in China from December 2022 to February 2023. Demographic information, clinical characteristics and outcomes were collected. Survival status was investigated at discharge and at 6 months after discharge. Results The mortality rate of COVID-19 patients with diabetes was higher than the rate of non-diabetic COVID-19 patients, both at discharge, and at 6 months after discharge. Body mass index (BMI), C-reactive protein (CRP), pH, D-dimer, blood osmotic pressure, serum creatinine, white blood cell count, creatine kinase and hospitalization expenses were significantly different between diabetic group and non-diabetic group (p < 0.05). Compared with the survivors, non-survived COVID-19 patients with diabetes had worse diabetes control indicators, with random blood glucose increased by 3.58 mmol/L (p < 0.05), and fasting blood glucose increased by 2.77 mmol/L (p < 0.01). In addition, there were significant differences in age, heart rate, CRP, pH, potassium (K+), serum creatinine, white blood cell count, creatine kinase, the proportion with diabetic complications, treatment in ICU and mechanical ventilation between survivors and non-survivors of COVID-19 patients with diabetes. By multivariate logistic regression analysis, the death of COVID-19 patients with diabetes is positively correlated with age and CRP (p < 0.05), and has a trend towards significance with fasting blood glucose (p < 0.1). Conclusion Infection with COVID-19 on the basis of diabetes can significantly increase mortality, which was further associated with diabetes control indicators.